2015
DOI: 10.3109/13880209.2014.982296
|View full text |Cite
|
Sign up to set email alerts
|

The growth and medicinal quality ofEpimedium wushanenseare improved by an isolate of dark septate fungus

Abstract: Context: Seven dark-septate endophytic (DSE) fungi have been isolated from the roots of Epimedium wushanense T. S. Ying (Berberidaceae), an important medicinal plant with various pharmacological activities. Objective: The current study explores the effects of seven DSE fungi on the growth and accumulation of bioactive compounds in E. wushanense. Materials and methods: Each 1-month-old E. wushanense seedling was inoculated with one of the seven DSE fungi and was grown under greenhouse conditions for 90 d. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The SEM analysis and variance partitioning showed that DSE significantly and directly influenced plant biomass, root surface area, and plant active ingredient and mineral nutrient content; DSE is the primary factor affecting the growth and active ingredients of liquorice. This was consistent with the findings of previous studies that DSE affect the growth and medicinal quality of medicinal plants (Wu et al, 2010; Zhang et al, 2012; Zhu et al, 2015). Meanwhile, to our knowledge, this study is the first to report the positive influence of P. putaminum as a plant pathogen on plant growth (Jiang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SEM analysis and variance partitioning showed that DSE significantly and directly influenced plant biomass, root surface area, and plant active ingredient and mineral nutrient content; DSE is the primary factor affecting the growth and active ingredients of liquorice. This was consistent with the findings of previous studies that DSE affect the growth and medicinal quality of medicinal plants (Wu et al, 2010; Zhang et al, 2012; Zhu et al, 2015). Meanwhile, to our knowledge, this study is the first to report the positive influence of P. putaminum as a plant pathogen on plant growth (Jiang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…However, nutrient deficiency and drought stress affects the quality and productivity of cultivated liquorice. To seek and apply effective methods for high-yield and high-quality plant material, recent studies have focused on investigating soil microorganisms that are beneficial to the medicinal plants (Zubek and Błaszkowski, 2009; Zhu et al, 2015). The beneficial effects of root-associated fungi such as arbuscular mycorrhizal fungi (AMF), dark septate endophytic (DSE) fungi, and Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, total root length, the diameter of primary roots, numbers and diameter of 2nd order lateral roots, root hair numbers and length varied significantly with different treatments. While the number and diameter of 1st order lateral roots and root hair diameter were not influenced by N. haematococca inoculation (Table 2), an increase in root length is also reported in Epimedium wushanense T. S. Ying inoculated with DSE fungi [20]. These observations are in direct contrast to a study where inoculation of the DSE fungus DSE48 reduced the root length and thickness of the tomato plant [21].…”
Section: Root Characteristicsmentioning
confidence: 62%
“…Relative to the control plants, P. putaminum increased the root biomass and root:shoot ratio, S. lignicola increased the shoot biomass and decreased the root:shoot ratio, and P. herbarum increased the root biomass. We propose that the growth-promoting efficacy of the DSE in their host plants varies with DSE species [33,34]. Previous studies reported that P. herbarum promotes plant growth by producing gibberellins [32].…”
Section: Effects Of Dse or T Viride Alone On The Growth Of Licorice mentioning
confidence: 99%